Design especulativo na política de educação de servidores públicos: um ensaio - Rizardi, Bruno Martins (2024)
The rapid pace of change makes the future increasingly uncertain, requiring the public sector to be able to anticipate and manage complexity in order to deliver good policies and services, especially with the implementation of emerging technologies such as artificial intelligence. Anticipatory governance has emerged as a model for this, using foresight tools to visualize different possible futures. However, its abstract nature limits its application to non-specialist actors. Speculative design, on the other hand, provides a methodology for "simulating" futures through speculative solutions, allowing for critical analysis of complex scenarios. Combining anticipatory governance with speculative design becomes a powerful tool for integrating artificial intelligence (AI) into the public sector. The aim of this paper is to explore the potential of combining anticipatory governance with speculative design for the incorporation of AI in the public sector, presenting a practical essay for reflection on its application, building hypotheses on the advantages and limitations of the approach, starting from the hypothesis that it is possible to contribute to the construction of methods and approaches that allow the preparation of a public sector capable of dealing with the uncertainties of the future, taking advantage of the opportunities of AI and applying it critically to deliver value to society. Based on a set of methodologies based on foresight and the practical application of speculative design tools on a real public policy, this study presents a first essay on the possibilities of incorporating speculative design as an anticipation tool in government, demonstrating its advantages and disadvantages in the context of public policies based on the use of artificial intelligence tools